Comfort food the cowboy way : backyard favorites, country classics, and stories from a ranch cook - Rollins, Kent; Rollins, Shannon (Harvest an Imprint of William Morrow, 2023)
"The stars of the YouTube channel Kent Rollins Cowboy Cooking and the authors of the hit cookbook A Taste of Cowboy share over 125 recipes of comfort food for the family, with true chuck wagon stories. While real-life cowboy Kent Rollins and his wife Shannon sure have a busy life on the range, slinging hash, beating Bobby Flay on Food Network, and running their YouTube channel, the Cowboy Kent Rollins Cooking Channel, they never forget to take a moment to break bread and share around the dinner table. Kent and Shannon's wisdom, warm generosity, and life-brightening humor is interwoven throughout Comfort Food the Cowboy Way, with stories and folklore from mid-American culinary history, cowboy life on the range, growing up in a rural family, and the interesting characters they've met on the trail: Grandma proudly serving Sunday dinner with family and friends gathered round, the short order chef at the hole-in-the-wall diner, whose classic comfort food makes a long car trip more than worthwhile, the grill man who knows how to coax fire-kissed deliciousness into every bite. The over 125 recipes included are equal parts hearty and scrumptious, from their classic Southern and Western favorites to the more spice-forward Tex-Mex and Bayou dishes. There's also backyard grilling and smoking, one-pot meals, and tips to add cowboy twists and authentic punched-up seasoning to all your cooking-and of course, all the recipes qualify as true comfort food the cowboy way, are easy-to-follow, and meant to be served up family style. With chapters spanning breakfast to dinner, plus grilling, desserts, and cowboy classics, this complete course of cowboy cooking is a must have for anyone wanting to slow down and enjoy a great meal, with even better company"--